qx+rx=s

Simple and best practice solution for qx+rx=s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for qx+rx=s equation:


Simplifying
qx + rx = s

Solving
qx + rx = s

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-1rx' to each side of the equation.
qx + rx + -1rx = -1rx + s

Combine like terms: rx + -1rx = 0
qx + 0 = -1rx + s
qx = -1rx + s

Divide each side by 'x'.
q = -1r + sx-1

Simplifying
q = -1r + sx-1

See similar equations:

| N-10+5n+6=32 | | 182x-0.02x^2+18000=0 | | 44-10n=6(-3n+2) | | 6+3y=15 | | 24=4*w*2 | | -10+8p+1+10p=9 | | -t*6=-7*8 | | (b+9)(b-12)=0 | | 5t+5=7t-4 | | -4-7+1= | | 6x^2-30x+11=0 | | -287=7(1+7n) | | 5y-2(y-6)=43 | | 24=4*w*3 | | -2=6a-4 | | 12x-7=24x+2 | | 2*56=-4 | | 2/5(25)-8=1/5(25)+7 | | 120w-23w=691 | | 1.25-0.3k+.5=1.3+0.5k | | 12x=11x-23 | | P-4+6+7p=74 | | 120w+23w=691 | | (-4-7)+1= | | b/13-3b/13=8/3 | | -16+18=-2(x+6) | | -4=-1-3 | | .5(4x+14)=2(2x-7) | | 125c^2-180= | | .4y+6=31 | | 0.5x-0.75y=-2 | | 9=6(x+6)-7x |

Equations solver categories